PENGARUH IKLIM ORGANISASI SEKOLAH TERHADAP KINERJA MENGAJAR GURU DI SMK NEGERI SE-KOTA BANDUNG - Romansyah, Rona (2015)
Penelitian ini berjudul: "Pengaruh Iklim Organisasi Sekolah Terhadap Kinerja Mengajar Guru di SMK Negeri se-Kota Bandung. Penelitian ini berangkat dari asumsi bahwa iklim organisasi sekolah mempengaruhi kinerja mengajar guru. Berdasarkan hal tersebut, Permasalahan yang hendak dipecahkan dalam penelitian ini adalah : Bagaimana gambaran iklim organisasi Sekolah di SMK Negeri se-Kota Bandung; Bagaimana gambaran kinerja mengajar guru di SMK Negeri se-Kota Bandung; serta Seberapa besar pengaruh iklim organisasi sekolah terhadap kinerja mengajar guru di SMK Negeri se-Kota Bandung. Metode yang digunakan dalam penelitian ini yaitu metode deskriptif dengan pendekatan kuantitatif dengan ditunjang studi kepustakaan. Teknik pengumpulan data menggunakan angket yang bersifat tertutup dengan skala empat. Sedangkan sumber data yang disajikan berupa sampel penelitian berjumlah 284 dari 284 data yang berhasil disebar. Teknik pengolahan data dilakukan dengan prosedur: menyeleksi data, mentabulasi data, mengukur kecenderungan skor responden menggunakan formulasi WMS, dan uji normalitas distribusi data. Selanjutnya melakukan pengujian hipotesis penelitian dengan prosedur: uji koefisien determinasi, uji signifikansi, uji analisis korelasi dan uji analisis regresi. Hasil penelitian menunjukkan bahwa kecenderungan skor rata-rata keseluruhan dari setiap indikator untuk variabel X (Iklim Organisasi Sekolah) adalah sebesar 3,05 dengan kategori sangat baik. Variabel Y (Kinerja Mengajar Guru) termasuk ke dalam kategori sangat baik pula dengan rata-rata skor sebesar 3,54. Berdasarkan perhitungan SPSS menunjukkan bahwa R Square sebesar 0,161, setelah dilakukan perhitungan dengan menguji koefiensi determinasi bahwa variabel Y (Kinerja mengajar guru di-Kota Bandung dipengaruhi sebesar 16,1 %dan 84,9% dipengaruhi oleh variabel lain. Dengan kata lain, terdapat pengaruh yang signifikan antara Iklim Organisasi Sekolah dengan kinerja mengajar guru SMK Negeri di-Kota Bandung. This study entitled: "The impact of School Organisation Climate on teacher's teaching performance in all public vocational school in Bandung". This study departs from the assumption that school organisation climate affect teacher's teaching performance. Based on that fact, the problem that need to be solved in this study are: How is school organisation climate pictured in all public vocational school in Bandung; How is the teacher's teaching performance pictured in all public vocational school; and how big is the impact of school organisation climate on the teacher's teaching performance in all public vocational school in Bandung. The goal of this study is to know the actual condition of school organisation climate in all public vocational school in Bandung, and to gather the comprehensive information about teacher's teaching performance in all public vocational school in Bandung and to obtain clear information about how big is the impact of school organisation climate on teacher's teaching performance in all public vocational school in Bandung. The methods used in this study is desciptive with qualitative approach supported by literature review. The data technique used in this study is in a form of confidential questionnaire with scaling from one to four. The data presented is in the form of research sample in total of 284 from 284 that have been succesfully distributed. The procedure for data processing techniques are: data selection, data tabulation, measuring the score tendency of respondents using formulation WMS (CMS), and data distribution normality test. Subsequently, conducting the study hypothesis with procedure: coefficient determination test, significance test, test correlation analysis, regression analysis test. The result of the study shows that teh tendency of the average overall score of each indicator for the variable X (School Organisation Climate) is equal to 3,05 with the excellent category. Variable Y (Teacher's Teaching Performance) also goes into the excellent category as well with the average score of 3,54. Based on SPSS calculations show that R Square of 0.161, after the calculation is done by testing coefficiency determination that the variable Y (Teacher's Teaching Performance in Bandung) influenced by 16.1% and 84.9% influenced by other variables. In other words, there is a significant influence between the School Organisation Climate with Teacher's Teaching Performance in all public vocational school in Bandung.